(untitled) (Bulletin KNOB, 1993)
In 1809 the village of Assen was granted the rank of town by king Louis Napoleon. The architect Jan Giudici (1746-1819) was commissioned to make an urban-development plan for Assen. All this was part of Louis’s aspirations to give an economic incentive to the regions in the country which were lagging behind. Assen was to become a junction of roads and waterways. In the town plan designed by Giudici hardly anything of the old village of Assen was left. Important elements in the plan were the central square, on which major buildings were situated, the harbour and the royal palace which had been planned outside of the town. The greater part of the town was to be composed of a pattern of rectangular rows of houses, to be expanded if the building urge of the citizens should give rise to it. A few elements of Giudici’s plan show similarities to the ideas of the French theoretician J.N.L. Durand, It is quite conceivable that Giudici knew Durand’s books through the court architect of Louis Napoleon, J.T. Thibault (1757-1826). Giudici’s ground plan of the royal palace reminds one of the designs by the Frenchman C.N. Ledoux (1736-1806). The plans for Assen were very ambitious and were never to be realized.